Psychological resilience and intention to stay among nurses: the mediating role of perceived organizational support - Pu, Jiangfeng; Wang, Waner; Li, Gege; Xie, Zhanghao; Fan, Xuanhao; Zhan, Ningjing; Xu, Yixuan; Huang, Huigen (Frontiers in Psychology, 2024)
The main purpose of this study is to analyze the relationship between psychological resilience, perceived organizational support, and intention to stay and to explore the mediating effect of perceived organizational support on psychological resilience and intention to stay in nurses.: A cross-sectional survey was conducted from August to September 2023 in which 1402 nurses from five Grade 3A Hospitals in Guangdong participated. The questionnaires used in the survey include the General Information Questionnaire (GIQ), the Chinese version of the Connor-Davidson Resilience Scale (CD-RISC), the Chinese version of the Perceived Organizational Support Scale (POSS), and the Chinese version of the Intention to Stay Scale (ITSS). The obtained data were analyzed through descriptive statistics, Pearson's correlation coefficient, and the mediating effect of perceived organizational support was tested through the PROCESS macro mediation model in SPSS.The overall mean of psychological resilience of nursing in five Grade 3A Hospitals in Guangdong is 60.54 ± 19.17, the overall mean of perceived organizational support is 45.77 ± 11.49, and the overall mean of intention to stay is 20.82 ± 4.65.Statistical analysis showed that there is a positive correlation between psychological resilience and intention to stay in nurses (r = 0.388, p < 0.01), between their perceived organizational support and psychological resilience (r = 0.570, p < 0.01), and between their perceived organizational support and intention to stay (r = 0.550, p < 0.01). The perceived organizational support of nursing has a mediated effect on the relationship between psychological resilience and intention to stay. The mediated effect value was 0.067, accounting for 71.28% of the total effect.The psychological resilience of nursing can have a direct impact on predicting the intention to stay and indirectly influences their caring behaviors mediated by perceived organizational support, with the latter effect being mediated by perceived organizational support. Therefore, nursing managers should have targeted interventions to enhance nurses' levels of psychological resilience and perceived organizational support, which could further increase nurses' intention to stay in their jobs, thereby improving the quality of care and creating a solid nursing workforce.